Antifungal activity of paeonol against Botrytis cinerea by disrupting the cell membrane and the application on cherry tomato preservation - Jiao, Yang; Zheng, Yu; Wu, Shiqin; Zhou, Li; Jiang, Hua; Li, Yuanhong; Lin, Fuxing (Frontiers in Microbiology, 2024)
Botrytis cinerea may cause gray mold in fruits and vegetables. Paeonol, an active component of traditional Chinese medicine, could suppress various microbial growth. However, reports on its effect on B. cinerea have not yet been documented. In this paper, we demonstrated that paeonol completely inhibited B. cinerea growth at 250 mg/L, corroborated by the observation of irregular morphological alterations in B. cinerea exposed to paeonol. Notably, the investigation of the operating mechanism revealed that paeonol induced cell death by disrupting the cell membrane, potentially mediated by the interaction between paeonol and ergosterol from the membrane. Further studies indicated that paeonol decreased ergosterol content and the expression of certain genes involved in ergosterol biosynthesis was significantly downregulated. In addition, paeonol treatment reduced the gray mold of cherry tomatoes. Meanwhile, compared to the control treatment, paeonol treatment could reduce weight loss and maintain higher contents of total soluble solid (TSS) and ascorbic acid, leading to a higher quality of the stored cherry tomato. Together, the data indicate that paeonol was effective as an alternative agent targeting disrupting the cell membrane to control gray mold and prolong the shelf life of cherry tomatoes, suggesting that paeonol could be used as a natural antifungal compound during postharvest storage.